Education and South Korea’s New Southern Policy: Locus and Prospects - Inero Ancho; Kyungeun Kim; Saehoon Park (Jurnal Studi Pemerintahan, 2021)
The implementation of South Korea's Southern Policy (NSP) has undoubtedly resulted in significant changes to the region's economic and political landscape. NSP may be viewed as a basis for Korea and a Southeast Asian nation to foster "co-prosperity and expand the scope for cooperation". This qualitative study makes use of policy document analysis as a methodology. The NSP serves as the primary source document for this research. The researchers evaluated the NSP in relation to the document's locus of education. Following that, these are examined in relation to the location and context. The locus of education analysis shows how NSP is typically moving southward in search of exchange. While education is included in certain requirements, it is viewed as restricted and insufficient in a variety of circumstances. The researchers have found other options to investigate in light of NSP's educational philosophy